Research progress on endoplasmic reticulum homeostasis in acute kidney injury - Hu, Liling; Chen, Huike (Frontiers in Pharmacology, 2025)
The endoplasmic reticulum (ER) is the most metabolically active organelle in cells, and recent research has shown that abnormal ER function is involved in the occurrence and development of acute kidney injury (AKI), but the underlying molecular mechanism needs to be further elucidated. Here, we review the biological functions of the ER in cellular metabolism, explore the current research progress on the role of the ER in different triggers of AKI, and summarize the ER stress inhibitors discovered thus far. Finally, we explore the possibility of targeting ER homeostasis as a therapeutic target for AKI.